PENGARUH MODAL SENDIRI TERHADAP LABA USAHA PADA KOPERASI SIMPAN PINJAM ARTHA JAYA DEPOK - Rina Apriliani (POLITEKNIK LP3I JAKARTA, 2018)
AbstractThis study aims to determine the effect of working capital in the form of cooperatives operating income of net income. And to produce a study of the processed information data on the extent to which and how much influence the working capital in the form of cooperatives operating profit of net income. The method used is the Facto Expose method with correlation approach and direct observations to the competent authority in the cooperative. Based on the analysis of the correlation coefficient, the value of r = 0.484 means that there is a moderate and positive influence which indicates that an increase in own capital can increase operating profit. As well as the calculation of the coefficient of determination produces kd = 23.5%. This means that 23.5% of the dependent variable, which is operating income, can be explained by an independent variable, namely equity. While the remaining 76.5% is explained by other factors not examined by this study such as the provision of credit, investment in the business sector, investment in banks and others.Keywords: working capital, wards profit, savings and loan cooperatives.